ANALISA STRATEGI BAURAN PEMASARAN PADA USAHA VENDOR WEDDING MENGGUNAKAN METODE SWOT (STUDI KASUS: ALEA DECORATION LAMPUNG BARAT) - Santia, Meri; Khikmawati, Emy; Anggraini, Melani (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2025)
The rapid development of the wedding industry requires every business actor, including wedding vendors, to adopt appropriate marketing strategies in order to remain competitive in an increasingly intense market. Alea Decoration Lampung Barat, as one of the wedding vendors, faces various challenges, both from internal factors such as limited design variations and insufficient offline promotion, and external factors such as price competition and the presence of informal vendors offering similar services. This study aims to analyze the marketing mix strategy (4P), which includes product, price, promotion, and place, and to formulate the appropriate marketing strategy through a SWOT analysis approach for Alea Decoration. This research employs a descriptive quantitative method, with primary data obtained through interviews and questionnaires distributed to 40 respondents, as well as secondary data sourced from relevant literature and publications. Validity and reliability tests were conducted using SPSS 26, and the results indicate that all instruments are valid and reliable (Cronbach’s Alpha of 0.992 for internal factors and 0.988 for external factors). The results of the IFAS and EFAS analyses show total scores of 4.044 and 3.438, respectively, placing Alea Decoration in Quadrant II of the SWOT matrix. This position suggests that the company possesses strong internal capabilities but faces significant external threats, thus the appropriate strategy to employ is the ST (Strength–Threat) strategy, which involves utilizing internal strengths to address market threats. The study shows that Alea Decoration’s main strengths lie in service quality, the ability to customize designs, and active digital promotion. Meanwhile, the greatest threat comes from competitors offering lower-priced services. Based on the analysis, several strategies are recommended, including enhancing design innovation, strengthening digital promotion, developing collaboration with other vendors, improving service quality, and expanding service coverage. The findings of this study are expected to serve as a strategic guideline for Alea Decoration and as a reference for similar businesses in developing effective and sustainable marketing strategies.